Reinventing identities: the gendered self in discourse - Bucholtz, Mary; Liang, A. C.; Sutton, Laurel A. (Oxford University Press, 1999)
Talk is crucial to the way our identities are constructed, altered, and defended. Feminist scholars in particular have only begun to investigate how deeply language reflects and shapes who we think we are. This volume of previously unpublished essays, the first in the new series Studies in Language and Gender, advances that effort by bringing together leading feminist scholars in the area of language and gender, including Deborah Tannen, Jennifer Coates, and Marcyliena Morgan, as well as rising younger scholars. Topics explored include African-American drag queens, gender and class on the shopping channel, and talk in the workplace.
Disponible en ligne à https://ebookcentral.proquest.com/lib/uqam/detail.action?docID=4702911 Donné en lecture au cours LIN2685, Barrett, Rusty. Indexing Polyphonous Identity in the Speech of African American Drag Queens, pp. 313-331.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; intersectionnalité; lin2685; linguistique; premier cycle; queer; ressource en ligne; sciences humaines; thématiques

Gender articulated: language and the socially constructed self - Hall, Kira; Bucholtz, Mary (Routledge, 1995)
Gender Articulated is a groundbreaking work of sociolinguistics that forges new connections between language-related fields and feminist theory. Refuting apolitical, essentialist perspectives on language and gender, the essays presented here examine a range of cultures, languages and settings. They explicitly connect feminist theory to language research. Some of the most distinguished scholars working in the field of language and gender today discuss such topics as Japanese women's appropriation of "men's language," the literary representation of lesbian discourse, the silencing of women on the Internet, cultural mediation and Spanish use at New Mexican weddings and the uses of silence in the Anita Hill-Clarence Thomas hearings.
Donné en lecture au cours LIN2685, Hall, Kira, Lip Service on the Fantasy Lines, pp321-342.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; maternité; premier cycle; queer; sciences humaines; sociolinguistique; thématiques; études de genres

Faut-il brûler les dictionnaires? - Yaguello, Marina (Les mots et les femmes : essai d'approche socio-linguistique de la condition féminine, 1992)
Keywords: cours; discipline; europe; fem1000; france; linguistique; perspectives féministes; premier cycle; régions géographiques; sciences humaines; sociologie; thématiques; écriture des femmes*

Les mots et les femmes : essai d'approche socio-linguistique de la condition féminine - Yaguello, Marina (Payot, 1992)
Comment les femmes parlent-elles ? Comment se parlent-elles ? Comment leur parle-t-on ? Et comment parle-t-on d'elles ? Les femmes et les hommes parlent-ils la même langue ? Quel rôle jouent la métaphore sexuelle, les connotations dépréciatives, les insultes à caractère sexuel comme véhicules de l'idéologie sexiste ? Ce livre tente de cerner le langage dans sa diversité sexuelle posée comme culturelle et non pas "naturelle".
Keywords: cours; discipline; europe; fem1000; france; linguistique; perspectives féministes; premier cycle; régions géographiques; sciences humaines; sociologie; thématiques; écriture des femmes*

Feminist practice and poststructuralist theory - Weedon, Chris (Blackwell, 1987)
Feminist Practice and Poststructuralist Theory offers a clear and accessible introduction to poststructuralist theory, focusing on questions of language, subjectivity and power.
Section: viii, 187 p
Keywords: 1900-1999; 1980-1989; cours; discipline; europe; fem1000; linguistique; post-structuralisme; premier cycle; périodes historiques; royaume-uni; régions géographiques; sciences humaines; théories féministes